Studying the Night Shift: A Multi-method Analysis of Overnight Academic Library Users - Schwieder, David; Spears, Laura I. (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2017)
Objective – This paper reports on a study which assessed the preferences and behaviors of overnight library users at a major state university. The findings were used to guide the design and improvement of overnight library resources and services, and the selection of a future overnight library site.Methods – A multi-method design used descriptive and correlational statistics to analyze data produced by a multi-sample survey of overnight library users. These statistical methods included rankings, percentages, and multiple regression.Results – Results showed a strong consistency across statistical methods and samples. Overnight library users consistently prioritized facilities like power outlets for electronic devices, and group and quiet study spaces, and placed far less emphasis on assistance from library staff.Conclusions – By employing more advanced statistical and sampling procedures than had been found in previous research, this paper strengthens the validity of findings on overnight user preferences and behaviors. The multi-method research design can also serve to guide future work in this area.